G143(P) A qualitative audit of paediatric patients and carers' experiences of urgent and emergency care. (25th October 2020) - Bowater, P; Mistry, R; Valentine, L; Schenk, D; Lim, E
Abstract : Aims: Attending the paediatric emergency department (PED) and acute assessment units can be a daunting and stressful experience for patients and carers. We aimed to evaluate their experience of PED and acute assessment unit visits. Methods: Data was captured using the validated RCPCH Patient Reported Experience Measure (PREM) for urgent and emergency care. This questionnaire was initially given out in 2013 and again in 2019 and included the views of patients, if over 8 years old, and/or carers. Completion of forms was voluntary and anonymised. In 2019 all respondents were offered the opportunity to take part in semi-structured interviews to explore their experiences in detail. Interviewees completed a questionnaire prior to the interview where they ranked the elements they most valued with regards to urgent care visits. This was used to scaffold the interview. Data was collected by 2 researchers, who transcribed verbatim, and by participants' written reports. In 2019 data was collected over a three-week period. All data collection and analyses were carried out by individuals independent from the clinical team. Qualitative data was thematically analysed by four researchers. This was the second part of an audit cycle. Results: In 2019 51 (18 involving patients) responses to the PREM questionnaire were collected and 12 interviews (4 involving patients) took place (20–30 minutes long). The majority described ED experience positively. From the PREM questionnaire key strengths included addressing pain in a timely manner and safety netting. Areas that need improvement include updates when waiting and advice on when to resume normal activities. From the interviews, communication and safety were identified as priorities. The provision of detailed information in a timely manner was highly valued, alongside feeling listened to by staff. Safety had three dimensions: physical, clinical and psychological/emotional. Waiting times and environmental factors also were valued but were less than other factors above. Conclusions: Communication is highly valued, but improvements are required to provide contemporaneous information. This is congruent with existing literature highlighting parent disempowerment in acute care settings and underlining the importance of timely updates. Good communication improved carers' feelings of psychological and emotional safety.